(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
This research dealt with the subject of auditing bank credit risks in accordance with international auditing standards and aims to develop procedures and design a credit risk audit program in accordance with international auditing standards and demonstrate their impact on the truth, truthfulness and fairness of financial statements and on their overall performance and continuity in the banking sector Its importance lies in relying on international auditing standards to assess and measure bank credit risk and its impact on the financial situation as well as the ability to predict financial failure. A set of conclusions have been reached, the most important of which is that the bank faces difficulties in measuring credit risk in accordance with international standards, including (the lack of a specialized electronic system, and the lack of Availability of a detailed database for each bank credit and recommendations, the most important of which is to work on applying international auditing standards in line with International Accounting Standard No. (9) For identifying and measuring the expected bank credit risks with a view to hedging them.